Exploring Computer Science Students’ Skill In Translating Technology and Computer Terminologies - Nida, Faridatun; Jiguang, Jiang; Azizah, Sindhy Nur (JEELS (Journal of English Education and Linguistics Studies), 2023)
This research explores the skill of computer-science students in translating technology and computer terminologies. It is a mixture of qualitative and quantitative. The data is collected by a survey. The participants are students of Amikom Purwokerto University. The analysis is executed using the Molina-Albir theory of translation techniques. It is then continued by evaluating the type of equivalency using theory from Kade. The result shows that the students' skill in translation varies. The techniques applied help the students to deliver the meaning from the source text to the target text. Unfortunately, only a half of the whole data reaches the total equivalence because of its changes in the form. Hence, the finding confirms that background knowledge of the participants in technology and computer science is provenly helpful to deliver and interpret the meaning. It also arisen an assumption that the combination of their knowledge and linguistics considerably can help the students in establishing the equivalency. Therefore, it is expected that the findings of the research give the novelty to the translation studies and also for the lecture in giving the lesson and activity for English and translation class because it is beneficial and gives contribution to solve the-real-world challenges.